2020
DOI: 10.3390/healthcare8030290
|View full text |Cite
|
Sign up to set email alerts
|

The Nutritional Status of Adult Antiretroviral Therapy Recipients with a Recent HIV Diagnosis; A Cross-Sectional Study in Primary Health Facilities in Gauteng, South Africa

Abstract: The study determined the nutritional status of adult antiretroviral therapy (ART) recipients, and investigated the association between the duration on ART and the nutritional status. This study was based in primary health facilities in Gauteng, South Africa. The data collected included sociodemographic variables; the duration of the treatment; and the body mass index (BMI), classified as undernutrition (<18.5 kg/m2), normal (18.5–24.9 kg/m2), or overweight/obesity (≥25 kg/m2). ART recipients (n = 480) had a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 46 publications
0
20
7
Order By: Relevance
“…However, the nding of the study indicated the magnitude of under nutrition obtained from our study was greater than study conducted south Africa, which is (13%) (19). The discrepancy could be due to socio economic and methodological approach.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…However, the nding of the study indicated the magnitude of under nutrition obtained from our study was greater than study conducted south Africa, which is (13%) (19). The discrepancy could be due to socio economic and methodological approach.…”
Section: Discussioncontrasting
confidence: 68%
“…In this study the magnitude of under nutrition among male were. 22% while 17.5% among women, the study conducted in south Africa proved that the prevalence of under nutrition was high, according the that study prevalence of under nutrition was higher in males (18%) than females (9%) (19).…”
Section: Discussionmentioning
confidence: 79%
“…This finding is in contrast to previous studies [36,37]. However, a recent study in South Africa showed that the likelihood of an HIV patient on ART being obese was dependent on a longer duration of the treatment [43] and the type of ART administered as some ART do not promote lipogenesis. Therefore, the lack of association between ART and obesity in this study might have been affected by the duration of ART use and the type of ART administered.…”
Section: Discussioncontrasting
confidence: 86%
“…Understanding the factors associated with underweight and overweight/obesity among women of childbearing age in Nigeria and South Africa would be useful for relevant health and non-health experts to implement evidence-based and appropriate interventions to address all forms of malnutrition. This context-specific information is also important to national and international stakeholders, given the contemporary obligation to accomplish SDG 3 to end all forms of malnutrition, as well as the Global Action Plan for the Prevention and Control of NCDs target 9 to reduce the overweight/obesity burden in both countries [ 19 , 20 , 21 , 22 ]. However, there is a dearth of research on the influence of urban–rural residence on women’s body weight in Nigeria and South Africa.…”
Section: Introductionmentioning
confidence: 99%